2021
DOI: 10.1371/journal.ppat.1009701
|View full text |Cite
|
Sign up to set email alerts
|

Control of SARS-CoV-2 infection after Spike DNA or Spike DNA+Protein co-immunization in rhesus macaques

Abstract: The speed of development, versatility and efficacy of mRNA-based vaccines have been amply demonstrated in the case of SARS-CoV-2. DNA vaccines represent an important alternative since they induce both humoral and cellular immune responses in animal models and in human trials. We tested the immunogenicity and protective efficacy of DNA-based vaccine regimens expressing different prefusion-stabilized Wuhan-Hu-1 SARS-CoV-2 Spike antigens upon intramuscular injection followed by electroporation in rhesus macaques.… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 67 publications
1
13
0
Order By: Relevance
“…Recent emerging Variants of Concern show a multitude of such changes which will likely affect NAb function of the WA1-induced antibodies. We and others reported that WA1 antibody showed lower binding to Delta both in humans (29,(33)(34)(35)(36)(37)(38) and vaccinated macaques (32).…”
Section: Discussionmentioning
confidence: 72%
See 3 more Smart Citations
“…Recent emerging Variants of Concern show a multitude of such changes which will likely affect NAb function of the WA1-induced antibodies. We and others reported that WA1 antibody showed lower binding to Delta both in humans (29,(33)(34)(35)(36)(37)(38) and vaccinated macaques (32).…”
Section: Discussionmentioning
confidence: 72%
“…Differences between slopes from consecutive intervals were also tested with the signed rank test. The fit model to deterrmine both the antibody endpoint titers and 50% titers of the neutralization curves were previously described (32) and were determinated using R methods-package (https://www.rdocumentation.org/packages/ stats/versions/3.6.2/topics/nls) (1). Analysis was performed by using GraphPad Prism Version 9.2 for MacOS X (GraphPad Software, Inc, La Jolla, CA).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In-house ELISA assays using a panel of purified trimeric complete Wuhan strain (WA1) Spike and Spike-RBD and a panel of VOC Spike-RBD proteins (Beta B.1.351, Delta B.1.617.2, Omicron B.1.1.529) were detailed elsewhere ( 26 28 ). Ab levels were measured using eight 4-fold serial serum dilutions starting at 1:50 and endpoint titers were determined using lastX feature using GraphPad prism area-under-the curve program.…”
Section: Methodsmentioning
confidence: 99%